Relevance of Ibn Taimiyah's Economic Thought on Fair Prices, Markets, and State Intervention from The Perspective of Islamic Economics - Salsabila Salsabila; Malahayatie Malahayatie (Journal of Indonesian Islamic Studies, 2026)
The rapid development of the global economy, marked by technological advancement, international trade, and dynamic consumption patterns, has created various real challenges, such as price fluctuations, monopolies, hoarding of goods, and unequal distribution of wealth. In this context, the principles of Islamic economics offer an alternative approach that emphasizes a balance between material profit, ethical values, and social responsibility in every economic activity. Ibn Taymiyyah (661–728 H/1263–1328 CE) made significant contributions to Islamic economic thought through the concepts of fair pricing (tsaman al-mithl), healthy market mechanisms, state supervision and intervention when necessary, and the fair management of property rights. This study employs a qualitative research method using a library research approach. The research data consist of primary sources in the form of Ibn Taymiyyah’s works, such as Al-Hisbah fi al-Islam, Al-Siyasah al-Syar’iyyah fi Ishlah al-Ra’i wa al-Ra’iyyah, and Majmu’ Fatawa, as well as secondary sources including books, scientific journals, articles, and previous studies relevant to the topic. The analytical technique used is descriptive-analytical analysis to examine Ibn Taymiyyah’s economic thought concerning fair pricing, market mechanisms, property rights, and the role of the state in Islamic economics. The findings of the study indicate that Ibn Taymiyyah acknowledged market mechanisms based on the interaction of supply and demand, while rejecting monopolistic practices, price manipulation, and hoarding that harm society. The state plays an important role through the institution of hisbah in supervising markets, maintaining price stability, ensuring fair distribution of wealth, and protecting public interests. The main finding of this study confirms that Ibn Taymiyyah’s economic thought remains relevant in addressing modern economic challenges through the implementation of an economic system that is fair, transparent, sustainable, and oriented toward social welfare in accordance with the perspective of Islamic economics.